Media Pembelajaran KIDAL pada Muatan Pembelajaran Bahasa Indonesia di Sekolah Dasar - Anri Nurahman; Salma Halidu; Candra Cuga (Universitas PGRI Semarang, 2022)
The problem that arises in this research is how the development and feasibility of KIDAL (Digital Audiovisual Comics) media in Indonesian subjects at SDN 3 Kota Barat and SD Integral Hidayatullah Kota Barat, Gorontalo City Is. This Study aims to develop KIDAL learning media and The purpose of this research is to develop KIDAL learning media and to determine the feasibilty of the developed media. This is a type of Research and Development study. Data were collected throught interviews and research instruments. The results of research on the development of KIDAL learning media based on media expert validation obtained a feasibility percentage of 93.5% with a very feasible interpertation, material expert validation obtained feasibilty percentage of 86% with a very feasible interpretation, and validation of learning practitioners/teachers obtained a feasibility of 97% with a very feasible interpretation. If the result of the validation of media experts, material expert, and learning practitioners are accumulated,the media developed obtains an average percentage of 92.2% with a very feasible interpretaion. From these results it can be conculded that the development of KIDAL learning media is very feasible to be used in the learning process and is able to improve student learning outcomes.